Autogestão e sustentabilidade na Cresol de Dois Vizinhos - PR: uma possibilidade alternativa? - Vasco, Ana Paula Debastiani (2012)
This work is bound to issue a joint research aimed at understanding the management of public policies or programs developed by non-governmental organizations (NGOs) or public bodies of two neighbors line up to the precepts of the development of family farming in a sustainable perspective. To do so was made a diagnosis socio-economic-environmental community Mazurana Farm, in order to understand the dynamics of the actions of these organizations in the life situation of the farmers of the community. Specifically, this work focused on the Rural Credit Cooperative Cresol. It is understood that there are theoretical and contextual evidence that may point out the social economy as an alternative proposal to the family farm. This model proposes a process of organizing economic and social self-management. Accordingly, we sought to understand how farmers understand and participate in cooperative self-management to identify how this model has led, or not, the sustainable practices of farming families. In this respect we identified good / reasonable conditions of the cooperative Cresol, mainly as a result of the Clean Water program accessed via the community and City Hall, it seemed, strategies mounted by the agricultures. Some trends were checked in the direction of the organization the illustrative case of two neighbors of Cresol-PR that can point to System guidelines Cresol.